Saw X [videorecording (DVD)] - Goldfinger, Peter; Stolberg, Josh, 1971-; Bell, Tobin; Smith, Shawnee; Lund, Synnøve Macody, 1976-; Brand, Steven, 1969-; Vaca, Renata; Beach, Michael, 1963-; Hernández, Paulette; Hinojosa, Octavio; Okamoto, Joshua (Lionsgate, 2023)
John Kramer is back. The most disturbing installment of the Saw franchise yet explores the untold chapter of Jigsaw's most personal game. Set between the events of Saw I and II, a sick and desperate John travels to Mexico for a risky and experimental medical procedure in hopes of a miracle cure for his cancer only to discover the entire operation is a scam to defraud the most vulnerable. Armed with a newfound purpose, the infamous serial killer returns to his work, turning the tables on the con artists in his signature visceral way through devious, deranged, and ingenious traps.